Mówione Magisterium Kościoła - kaznodziejstwo Papieża Franciszka - Rafał Kowalski (Colloquia Theologica Ottoniana, 2018)
The author of the text, by the analysis of Pope Francis’s homilies, seeks the answer for the question: what makes the homilies so willingly received by the faithful and widely discussed by journalists, especially, if you take into consideration that the Holy Father often criticizes the Europeans’ lifestyles. This search is based on the anthropological approach to the proclamation of God’s Word (keeping in mind the theological aspect of this reality), and especially, the so called communication square by Friedman Schluz von Thun. On this basis, particular statements of the Bishop of Rome are analyzed, and the secret of the effectiveness of Pope’s speeches – in the author’s opinion – is in the draws attention not only to the contents of the homilies and catechesis, but primarily to what the Pope says about himsef, how he treats his listeners, and how he calls for particular actions. The author concludes that Francis does not call the faithful out on who they are not, but he helps them understand who they became through God’s grace, and who they can become if they allow God act in their lives.